Record of Alternaria tenuissima as a causal pathogen of Leaf Spots in Chard Plant in Basrah, Iraq, and It’s In vitro Management - Alaa O. Manea; Anna D.khamas; Mohammed A.Fayyadh; Hajra Azeem (University of Thi-Qar Journal of agricultural research, 2023)
The chard plant is an important vegetable crop, thus this study aimed to isolate and identify Alternaria tenuissima and efficiency evaluation of Pseudomonas fluorescens, Trichoderma viride, Trichoderma harzianum, and Paecilomyces fumosoroseus suppression against A. tenuissima. T. harzianum demonstrated its ability to inhibit the A.tenuissima by 63.8%. Also, it reduced the leaf spot number to 0.39 cm/leaf compared to the control that scored 2.19 cm/leaf. The T. harzianum increased the leaves and root weight, followed by P fluorescens treatment. This is considered the first recorded in Basra, Iraq.